The Influence of Career Planning, Work Interest and Self-Efficacy on Student Work Readiness (Case Study of Private University Students in Semarang City) - Saputri, Enun Fatmah; Ervina Indiworo, Rr Hawik; Dharmaputra, M Fadjar (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the influence of career planning, work interest and self-efficacy on the work readiness of Private University students in Semarang. This type of research is quantitative research. The population in this study were private university students in Semarang with a sample size of 100 respondents. The sampling technique uses non-probability sampling. The data collection technique is in the form of a questionnaire which is processed using the IBM SPSS version 22 application. The data analysis technique uses multiple linear regression. The results of the research show that there is a positive and significant influence between career planning on student work readiness, there is a positive and significant influence between work interest on student work readiness, there is a positive and significant influence between self-efficacy on student work readiness. The results of the R coefficient of determination test obtained an Adjusted R Square value of 0.591 or 59.1%.